PERFORMING LEGISLATIVE FUNCTIONS: THE ROLE OF REGIONAL REPRESENTATIVE COUNCIL AND PEOPLE'S REPRESENTATIVE COUNCIL - Gunawan, Bambang Panji; Zamroni, M.; Miarsa, Fajar Rachmad Dwi; Mangesti, Yovita Arie (YURIS: Journal of Court and Justice, 2023)
Based on two factors, these are philosophical and legal aspect. In terms of the function of law, the existence of the Regional Councilor (DPD) and Legislative Assembly (DPR) can be established. Based on a provision in the 1945 Constitution, the Regional Councilor (DPD) and Legislative Assembly (DPR) were established, and, according to one philosophical definition, they represent all regional or people's representatives in Indonesia at the national scale. A system of functional industrial relations exists between the Regional Councilor (DPD) and Legislative Assembly (DPR) in relation to the function of legislation. The objective of this research are to find out the role of Regional Councilor (DPD) perform in the legislative functions; and Legislative Assembly (DPR) represent in obtaining legal products. The research that was accomplished was categorized as qualitative normative research based on the kind of data or legal materials examined. Due to institutional and constitutional limitations, the Regional Councilor (DPD) and Legislative Assembly (DPR) faced difficulties as a result of legal responsibilities. Institutional constraints are limitations imposed by the institution itself, such as insufficient support systems, unsuccessful legislation, and ineffective session management techniques. The Regional Councilor (DPD)'s current rules, Article 22D, paragraphs 1 and 2, and Law No. 27/2009 on MD3 are among the challenges we must overcome. These laws attempt to undermine the legislative authority of the Regional Councilor (DPD).